Recombinant Ns3 Serine Protease From Dengue Virus 2 As A Screen For Small Molecules - Ab Aziz, Nurohaida (2011)
Dengue infection is re-emerging as a major global disease and is classified as a Category A priority pathogen. Dengue viruses are estimated to infect 50-100 million people annually and are considered to cause one of the most important arthropod-borne viral diseases in terms of human morbidity and mortality. Virus transmission occurs through the bite of the Aedes aegypti mosquito and half the world’s population is at risk for infection. There is presently no approved vaccine or antiviral drug that is effective against dengue viruses. The focus of this thesis is to combine the power of high performance computing with wet lab experiments for the recombinant NS3 serine protease from dengue virus type 2 as a screen for antiviral small molecules that can be used either to prevent or treat dengue virus infections.